Development of Learning Strategies to Integrate Computational Thinking in Early Childhood Education Curriculum: A Study on 36 Early Childhood Education Units in Kudus - Yuliantina, Irma (JURNAL PENDIDIKAN USIA DINI, 2025)
Indonesia's low achievement in international assessments such as PISA shows the need to strengthen high-level thinking skills from an early age. One of the important competencies of the 21st century is computational thinking, which is a logical and systematic framework of thinking in solving problems. This research aims to develop a learning strategy to integrate computational thinking skills into the Early Childhood Education (PAUD) curriculum. The research was carried out in 36 partner PAUD units in Kudus Regency, Central Java, using the Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research subjects consisted of school principals and PAUD teachers. The development process lasted for eight months, starting with training related to the concept of computational thinking, its relationship with the Independent Curriculum, and its implementation strategy in classroom learning. The results of the study show that teachers need clear and practical guidance to integrate computational thinking skills into learning activities that are in line with the Independent Curriculum. This research does not produce a new curriculum product physically, but gives birth to a model of learning strategies that are conceptual and implementive. The strategy includes steps to prepare a plan, organize the play environment, and provide teacher support that encourages children's computational thinking skills. Implementation in the field showed a positive impact on teacher understanding, child involvement, and parental response, although challenges were still found in a small number of PAUD units. This research makes a concrete contribution to strengthening adaptive and future-oriented PAUD learning practices.